Import demand potential for Indonesian rubber products in ASEAN countries - Zainuddin Zainuddin (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2022)
Increasing imports of rubber products from Indonesia is the key to the success of the downstream policy of rubber products to gain added value and job opportunities in the country. The rubber product market in ASEAN is more dynamic, and Indonesia must focus on strengthening competitiveness and exploiting potential markets. This paper aims to describe the potential demand for imports of Indonesian rubber products in ASEAN countries, especially Malaysia, Singapore, Thailand, the Philippines, and Vietnam. The flow of imports of rubber products uses the stochastic frontier panel data model to determine the potential demand for imports of Indonesian rubber products. Indonesian rubber products compete fiercely with similar industries in importing and exporting countries from East Asia. Indonesia mostly exports rubber products with HS codes 4015 and 4016 in the form of gloves, mittens, and mitts, rubber cellular, floor coverings and mats, erasers, gaskets and rings, boats, and fender docks to all markets in ASEAN countries. They were followed by rubber products with HS code 4010 in the form of conveyor belts or transmission belts from vulcanized rubber. The potential for import demand for other types of Indonesian rubber products (code HS4014, 4009, 4008) in ASEAN countries is relatively small and is growing slowly. Overall, the potential demand for imports of Indonesian rubber products tends to decline in ASEAN countries, as well as the actual imports of rubber products from Indonesia compared to their potential, which also declines slowly.